Comparative Failure Assessment of Single and Double Lap Joints with Varying Adhesive Systems. Issue 7 (1st September 2016) - Nunes, S.L.S.; Campilho, R.D.S.G.; da Silva, F.J.G.; de Sousa, C.C.R.G.; Fernandes, T.A.B.; Banea, M.D.; da Silva, L.F.M.
Abstract : Joining by adhesively bonded methods is being increasingly used in the design of mechanical structures, because of the significant benefits of this technique compared to the traditional ones. Commercial adhesives range from strong and brittle (e.g., Araldite ® AV138) to less strong and ductile (e.g., Araldite ® 2015). A new family of polyurethane adhesives combines high strength and ductility (e.g., Sikaforce ® 7888). This work compares the tensile performance of the three aforementioned adhesive systems in single and double lap aluminum joints with varying values of overlap length ( L O ). A cohesive zone modeling (CZM) numerical analysis was carried out to analyze through-thickness normal and shear stresses in the adhesive layer, to study the CZM damage variable and to predict the joint strength. A comparison was also performed with simple analytical models. The stress and damage variable analyses helped in understanding the differences between adhesives in which pertains to the failure process and joint strength. The proposed work also enabled concluding that the CZM predictions are typically accurate, and which family of adhesives is more suited for each joint configuration, with clear advantage for the Sikaforce ® 7888. As a result of this work, design guidelines were proposed for adhesively bonded joints.